1-D Simulation of Ultrafast-Pulsed Laser into Nano-Sized Multilayered Structure (Ni81Fe19/Cu/YIG/GGG) for Memory Device Applications - Abdul-Hussain, Muhaiman A.; Mohamad, Haidar J.; Al-Haddad, Ahmed (Iraqi Journal of Science, 2022)
Spintronic offers a solution by exploiting spin instead of electron charge since spin current propagation can occur in principle without dissipation. One of the applications involve within this project for storage media is heat-assisted magnetic recording (HAMR). The objective of this study is to simulate the behavior of thermal gradient to generate a pure spin current using an ultrafast femtosecond (fs) laser in a nano-sized  multilayered structure of (Al2O3/Ni81Fe19 (Py)/Cu/Y3Fe5O12 (YIG)/Gd3Ga5O12 (GGG)) at room temperature. A ferromagnetic/spacer/magnetic insulator nano-sized multilayered is the proposed structure for this study. Electron spin, directed by the external applied magnetic field, is transferred via the spacer to the magnetic insulator, leading to the generation of a spin-wave within the last layer. The ultrafast laser generates a spark of spin diffusion to get spin current. The thermal behavior within the trilayer simulated using COMSOL Multiphysics (v 5.5) is presented and supported by the theoretical model. Simulation results showed the effect of thickness and time on the generated spin current. Moreover, the thickness of the permalloy layer plays an essential role in generating a high-temperature gradient within a magnetic insulator to generate a spin current.